Linking Individual and Organizational Islamic Work Ethics to Employee Commitment: The Mediating Role of Perceived Organizational Support in Islamic Banks - Hawwa, Mohammad Said; Alzghoul, Amro; AL Jedi, Mohammad (International Review of Management and Marketing, 2026)
This research investigates the relationship between Islamic Work Ethics (IWE) and employee commitment, with a particular interest in the mediating effect of perceived organizational support (POS) within the Jordanian Islamic banks. Drawing upon the theory of organizational support as well as the social exchange theory, the study conceptualizes IWE as a multidimensional concept that comprises the individual level of ethical orientations and organization-level ethical practices. A quantitative methodology was used, and the data was gathered using a structured survey that was administered to the employees employed in Islamic banking institutions in Jordan. A total of 312 usable responses was analyzed by (PLS - SEM). The results demonstrate that individual and organizational dimensions of IWE have significant positive impacts on the perceptions of organizational support by employees. As a result, organizational support as perceived by employees was found to have a strong and positive influence on employee commitment. In addition, the analysis confirms the role of POS as a significant mediating mechanism in the relationship between IWE, at both levels, and commitment in employees. These results suggest that Islamic ethical values increase employee commitment by strengthening mainly perceptions of organizational support, but not directly. The research contributes to the literature by extending previous research studies on IWE beyond a one-dimensional perspective and also combining ethics values with organizational support mechanisms. From a practical perspective, the results indicate the significance of institutionalizing Islamic moral principles in organizational policies and practices, as such institutionalization may provide validation of perceived support and promote continued commitment of employees in Islamic banking organizations.